A experiência do parto no Sistema Único de Saúde : percepções de mulheres - Vidal, Renata Moura da Silva (2017)
The search for information concerning both the physiology of childbirth and the rights of pregnant women may contribute to the empowerment of these women. However, the high number of unnecessary cesarean in obstetric care, as well as interventions in labor together with obstetric violence, may hinder this empowerment. This study aims to, intersubjectively, analyze childbirth experiences in the Unified Health System (UHS) from the experience of some women in São Carlos – SP. Its specific objectives are to identify the elements that help to enable and the elements that may hinder childbirth experiences and also to understand the influence of other women’s childbirth experiences, moreover, providing recommendations for improving obstetric care. The Communicative Methodology was chosen for this study. The data collection instruments were the communicative report and communicative discussion group. Data analysis was performed together with the participants, who have the same interpretative capacity as the researcher, but at different levels of understanding. The elements identified as enablers and hindrances were classified under System and World of Life, terms previously defined by the method. The results show that childbirth assistance has improved, but strategic changes are still needed. Therefore, the lack of integrated actions has put care quality in jeopardy.